2021
DOI: 10.1111/jfpp.15246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ghee and olive oil usage on cocoa hazelnut spreads during storage

Abstract: Cocoa spreads are widely consumed delicious products, especially in breakfasts, consumed with pleasure by people of all ages and segments. They are eaten mostly as a spread on slices of bread, toasts, or used in similar pastries such as muffins and pitas and also used as fillings in biscuits and such products. They are expected to taste like chocolate and not to solidify at room temperature. This distinctive property is maintained by mixing considerable amounts (i.e., higher than 40% wt/wt) of oils and fats wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 16 publications
4
13
0
Order By: Relevance
“…The FFA values ranged between 0.21% and 0.47% during 9 months of storage. These values are lower than the FFA values (0.64%-0.80%) found for cocoa hazelnut spreads produced using ghee and olive oil and stored for 180 days (Tarakçi & Yildirim, 2021) The fatty acid profile of cocoa hazelnut spreads varies depending on the oil used for their production. Here, the predominant fatty acids in the cocoa hazelnut spread samples are palmitic (C 16:0), cis oleic (C 18:1 ω9), and cis linoleic acid (C 18:2 ω 6) (Table S1).…”
Section: Re Sults and Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The FFA values ranged between 0.21% and 0.47% during 9 months of storage. These values are lower than the FFA values (0.64%-0.80%) found for cocoa hazelnut spreads produced using ghee and olive oil and stored for 180 days (Tarakçi & Yildirim, 2021) The fatty acid profile of cocoa hazelnut spreads varies depending on the oil used for their production. Here, the predominant fatty acids in the cocoa hazelnut spread samples are palmitic (C 16:0), cis oleic (C 18:1 ω9), and cis linoleic acid (C 18:2 ω 6) (Table S1).…”
Section: Re Sults and Discussionmentioning
confidence: 59%
“…On the contrary, Acan, Toker et al (2021) found higher a * values ranging from 9.6 to 11.6 and lower b * values ranging from 1.04 to 3.93 in the chocolate spreads with the hazelnut cake. Tarakçi and Yildirim (2021) reported higher a * and b * values (13.24–14.98 and 13.29–15.13, respectively) in the cocoa hazelnut spreads produced using ghee and olive oil.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, it did not change in both groups during storage. In the study of Tarakçi and Yildirim (2021), cocoa hazelnut spreads developed using different oil types (palm, olive, ghee, and sunflower) and sensory analysis were performed on the 3rd, 90th, and 180th days.…”
Section: Color Properties and Sensorial Characteristicsmentioning
confidence: 99%